Executive summary of the KDIGO 2022 Clinical Practice Guideline for Diabetes Management in Chronic Kidney Disease: an update based on rapidly emerging new evidence - Rossing, Peter; Caramori, M Luiza; Chan, Juliana C N; Heerspink, Hiddo J L; Hurst, Clint; Khunti, Kamlesh; Liew, Adrian; Michos, Erin D; Navaneethan, Sankar D; Olowu, Wasiu A; Sadusky, Tami; Tandon, Nikhil; et al. (Kidney international, 2022)
The Kidney Disease: Improving Global Outcomes (KDIGO) 2022 Clinical Practice Guideline for Diabetes Management in Chronic Kidney Disease (CKD) represents a focused update of the KDIGO 2020 guideline on the topic. The guideline targets a broad audience of clinicians treating people with diabetes and CKD. Topic areas for which recommendations are updated based on new evidence include Chapter 1: Comprehensive care in patients with diabetes and CKD and Chapter 4: Glucose-lowering therapies in patients with type 2 diabetes (T2D) and CKD. The content of previous chapters on Glycemic monitoring and targets in patients with diabetes and CKD (Chapter 2), Lifestyle interventions in patients with diabetes and CKD (Chapter 3), and Approaches to management of patients with diabetes and CKD (Chapter 5) has been deemed current and was not changed. This guideline update was developed according to an explicit process of evidence review and appraisal. Treatment approaches and guideline recommendations are based on systematic reviews of relevant studies and appraisal of the quality of the evidence, and the strength of recommendations followed the "Grading of Recommendations Assessment, Development and Evaluation" (GRADE) approach. Limitations of the evidence are discussed, and areas for which additional research is needed are presented.